Charge distributions of fission fragments of low- and high-energy fission of Fm, No, and Rf isotopes; Physical Review C; Vol. 97, iss. 3 - Pasca H. Horia; Andreev A. V. Aleksandr Vasiljevich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich (2018, 2018)
Title screen